(untitled) (Academicia Globe: Inderscience Research, 2023)
A variety of pathology of newborns, associated with their intrauterine development, with the peculiarity of the course of childbirth, and giving severe complications in the neonatal period and in subsequent periods of childhood, dictates the need to improve the system of medical care. It is necessary to clearly deal not only with newborns, but also by studying the characteristics of the course of pregnancy, the nutrition of pregnant women and the impact of various diseases of the mother on the development of the fetus, it is possible to predict in advance the possibility of a child being born with certain diseases, in particular, intrauterine chronic eating disorders, and also to draw up an action plan for the prevention of expected pathologies associated with adverse factors in the antenatal, intranatal and neonatal periods of fetal and child development.